2014
DOI: 10.1007/s12105-014-0550-8
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Primary Osteosarcoma of the Larynx and Case Report

Abstract: Sarcomas of the larynx are exceedingly uncommon, of which primary laryngeal osteosarcomas are the rarest. To date, 25 cases of primary laryngeal osteosarcomas have been reported in the literature. Laryngeal osteosarcomas may closely simulate sarcomatoid carcinomas, since both entities share clinical, histological and immunohistochemical features. Herein, we report a case of primary laryngeal osteosarcoma in a 55 year old male, focusing on the importance of light microscopic, immunohistochemical and ultrastruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
6

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 30 publications
(62 reference statements)
0
14
0
6
Order By: Relevance
“…Среди последних можно выделить саркомы, которые имеют не только различное происхождение (мезенхимальные), но и различный патогенез. Саркомы гортани составляют всего 0,32-1 % от всех гортанных новообразований [1]. Наиболее распространены хондросаркомы и фибросаркомы.…”
Section: Introductionunclassified
See 3 more Smart Citations
“…Среди последних можно выделить саркомы, которые имеют не только различное происхождение (мезенхимальные), но и различный патогенез. Саркомы гортани составляют всего 0,32-1 % от всех гортанных новообразований [1]. Наиболее распространены хондросаркомы и фибросаркомы.…”
Section: Introductionunclassified
“…Всего за 1942-2014 гг. в мировой научной литературе представлено только 26 наблюдений остеогенных сарком гортани, по 1-2 в крупных онкологических клиниках [1]; например, с 1989 по 2008 г. в отделениях патологии и гистологии клиник Италии зафиксирован только 1 случай остеогенной саркомы гортани [8]. В отличие от остеосарком скелета, остеосаркомы гортани в основном встречаются у пожилых мужчин [3,4].…”
Section: Introductionunclassified
See 2 more Smart Citations
“…Compared to its more frequently involved subsites, the mandible and maxilla, 1 osteosarcomas make up <1% of all laryngeal cancers with the largest review citing only 26 cases since first reported in 1942. 2,3 Treatment of this rare disease has ranged from total laryngectomy to definitive radiation as extrapolated from paradigms of common osteosarcomas as well as more common malignancies of the head and neck. This report provides the most comprehensive review of reported cases (Table 1) and in-depth analysis to date.…”
Section: Introductionmentioning
confidence: 99%